Potential Growth in Colombia - Lanau, Sergi (IMF Working Papers; Working Paper, 2017)
This paper uses a multivariate filter and a production function to project potential growth in Colombia, modeling in detail the impact of low oil prices on investment. The framework also captures the impact of current and planned policies on potential growth, including the peace agreement with the FARC, the tax reform, and 4G infrastructure projects. The analysis suggests the growth acceleration of the 2000s is unlikely to repeat itself in a world of lower oil prices. Potential growth is likely to moderate to a range of 2.8 to 4.1 percent. The 4G infrastructure projects and the tax reform will increase investment, partly offsetting the sharp decline in oil investment. Improvements in productivity are essential to lift potential growth, as the large increases in the labor force observed in the last 15 years are unlikely to continue.